The Effectiveness of The Motor Vehicle Tax Tracker Team in Rawalumbu District, Bekasi City - Rissa Ayu Cameliawati; Ratih Kumala Ratih (Yayasan Ilomata, 2021)
The number of motorized vehicles has increased from year to year, but this has not been matched by the increase in the number of vehicles that have re-registered at the SAMSAT (One Stop Integrated Service) Office in Bekasi City. With the activities of the investigating team, the investigating team plays an important role especially for tax actors who do not re-register at SAMSAT Bekasi City, where they remind taxpayers to pay motor vehicle tax. This study aims to analyze the effectiveness of the motor vehicle tax inspection team as well as the obstacles and efforts made in increasing motor vehicle tax revenue in Rawalumbu Village, Bekasi City. The author uses the theory of David Krech, Richard S, Cruthfied and Egerton L. Ballachey Danim (2012: 119-120) in a book entitled Leadership Motivation and Effectiveness. This research is expected to be useful academically and practically. The method used in this research is descriptive qualitative. The results showed that the performance of the motor vehicle tax inspection team in Rawalumbu Village, Bekasi City was effective when measured by Beni Pekei's (2016) effectiveness criteria with a score of 100.38%. The obstacles faced in the effectiveness of the investigating team are the distance that is too far, the taxpayer's data is not up to date, and inadequate supervision by P3DW and SAMSAT. Meanwhile, efforts have been made, among others, Rawalumbu Village to cooperate with investigative teams and sub-districts to update taxpayer data periodically and to conduct socialization and education to taxpayers.